(untitled) (Window of Public Health Journal, 2025)
According to the statement of the Association of Indonesian Cosmetic Companies and Associations (PPA Cosmetics Indonesia), cosmetic users in Indonesia reach 126.8 million people. There was an increase from 2020 by 5.9%, and it is predicted that in 2023, it will continue to experience growth accompanied by the latest trends and types of products. In addition, the growth in Indonesian cosmetics industries reached 21.9%, namely 913 companies in 2022; in mid-2023, there were 1,010 companies. Of the total products of local cosmetic companies, the largest market segment is the personal care segment, with a market volume of USD3.18 billion in 2022, followed by skin care of USD2.05 billion, cosmetics of USD1.61 billion, and fragrances of USD39 million. This study is a cross-sectional study. The population in this study was 69 residents of Rappokalling Village, Makassar City. The sampling technique was purposive sampling, which means selecting research subjects based on special characteristics of the research objectives. Data analysis using Univariate and bivariate, There is a relationship between the frequency and duration of use of bleaching cream to mercury in hair in homemakers in appalling sub-district P = 0.000 ≤ α (0.05). Users complained about using bleaching cream, such as irritation, acne, and stinging. It is the responsibility of health workers from both health centers and the Makassar City Health Office to be more active in providing health services in the form of health education regarding the health impacts that will occur if mercury cream is used for a long period of time. This study highlights the crucial role of health professionals in addressing this issue. It is hoped that further researchers will expand research related to heavy metal mercury such as in blood, urine and so on.